Who Takes Care of Family Members Who Take Care of Older Dependent Adults? - Andrea del Pilar Comelin Fornés (Íconos)
The increase in the population of older adults in Chile reveals the importance of implementing social policies that guarantee their citizenship rights. An issue that is scarcely touched upon is the situation of the family members who care for older dependent adults. From the perspective of the social organization of care, data is analyzed in a study with quantitative and qualitative methodologies that describes the socio-demographic characteristics of the family caregivers of older, dependent adults of the Alto Hospicio commune hospital in Tarapacá and the aspects that facilitate or obstruct the exercise of the caregiver’s role from his or her point of view. The results provided demonstrate the need for a more active participation of the State through the design of public policies that allow caregiving to transcend the private family sphere, that activate primary and institutional networks, and that consider the caregiver and not only the older adult as a focal subject.